Length-weight relationships and ponderal index of three reef fish (Teleostei: Labridae) off the Tanjung Tiram coast, Southeast Sulawesi, Indonesia - Asriyana Asriyana; Nur Irawati; Halili Halili (Biodiversitas Journal of Biological Diversity, 2020)
Abstract. Asriyana A, Irawati N, Halili H. 2020. Length-weight relationships and ponderal index of three reef fish (Teleostei: Labridae) off the Tanjung Tiram coast, Southeast Sulawesi, Indonesia. Biodiversitas 21: 1279-1286. Parameters of length-weight relationship and ponderal index were estimated for first time for three reef fish (Labridae), Cheilinus trilobatus, Cheilinus chlorourus, and Choerodon anchorago, off the Tanjung Tiram coast, Indonesia. A total of 292 specimens (C. trilobatus 146 specimens; C. chlorourus 100 specimens; C. anchorago 46 specimens) were collected monthly in experimental gillnets in coral reefs and seagrass beds from January to June 2018. The length-weight relationship and ponderal index were calculated for each species. C. trilobatus showed total length and weight of 9.0-17.2 cm and 12.33-78.79 g, respectively, while C. chlorourus was 8.5-17.5 cm and 10.41-100.21 g, and C. anchorago 9.0-27.0 cm and 18.51-414.00 g. C. trilobatus showed negative allometric growth, while C. chlorourus and C. anchorago had isometric growth. The length-weight relationship of C. trilobatus followed the linear equation of W=0.10TL2.35, while C. chlorourus and C. anchorago fit to W=0.03TL2.83; W=0.03TL2.91 respectively. The highest ponderal index occurred in May for C. trilobatus and in June for C. chlorourus and C. anchorago indicating a peak of the spawning season. The study results could be used as baseline information for future fisheries management of the area.